29-Years Old Woman Presenting with ST Elevation Myocardial Infarction - Dyah Wulan Anggrahini; Budi Yuli Setianto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2015)
Myocardial infarction in young female is rare condition, but carries significant morbidity and mortality. The recognition management for MI in young female is challenging due to its unspecific clinical presentation and lack of guidance in the current guidelines. We reported a 29-years old woman presenting with infarction type chest pain, showing ST- elevation in the inferior leads with total AVblock as complication. The risk factors in this patient were smoking, family history, cardiomyopathy, and preeclampsia history. The cause for myocardial infarction in this patient was atherosclerotic plaque rupture, but we did not manage to performed coronary intervention due to her low ventricular function and unavailability data for myocardial viability at the time of hospitalization.